Distribution of the endemic species Astragalus babatagi Popov and growth characteristics of the plant in the Conditions of Tashkent (Uzbekistan) - Zakirova, Rano; Kurbanova, Elvira; Egamberdiev, Akmal; Nigmatullaev, Alim; Ergashev, Bekzod; Khojimatov, Olim; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2025)
Background: Astragalus plants, due to their medicinal properties, are widely used in traditional medicine across various cultures. Endemic and rare species represent a particularly vulnerable category due to intensive and unsustainable harvesting of raw materials. Among them is Astragalus babatagi Popov, a member of the genus Astragalus in the family Fabaceae. Like other species of this genus, it is a rich source of biologically active compounds such as cycloartane glycosides and flavonoids. One of the ways to conserve this category of medicinal plants is through cultivation. Methods: The objective of this study was to investigate the distribution of Astragalus babatagi in southern Uzbekistan, examine the plant's growth characteristics under Tashkent conditions, and analyze the elemental composition of its aerial and root parts. The habitat range of the endemic species Astragalus babatagi was studied, and a distribution map for A. babatagi was created based on materials from the Central Herbarium of Uzbekistan and expedition data using the Gisinfo.ru program. Results: The potential for cultivating this plant in Tashkent conditions was demonstrated. It was found that sowing scarified seeds of A. babatagi yields viable plants with high growth parameters. The developmental phases of plants growing at an altitude of 1700 meters above sea level were identified under Tashkent conditions. The elemental composition of the aerial and root parts of wild and cultivated plants was studied. The results confirm that A. babatagi has significant adaptive potential, allowing it to successfully grow and develop in urban conditions in Tashkent. Keywords: Astragalus babatagi, distribution range, cultivation, scarification, developmental phases, productivity, chemical elements